Design and Feasibility Evaluation of the TAPTAP Digital Platform for Measuring Port Service User Satisfaction at KSOP Bontang - Herdandy Octabrilian Putra; Rizqi Aini Rakhman; Sri Mulyanto Herlambang; Trisnowati Rahayu (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study designs and evaluates the feasibility of the TAPTAP digital platform, a Figma-based prototype for measuring port service user satisfaction at the Bontang Harbormaster and Port Authority Office (KSOP Bontang). The study used a Research and Development (R&D) approach adapted into six stages: problem identification, information collection, product design, design validation, design revision, and product trial. Data were gathered through field observation, document review, stakeholder input, and expert feasibility assessment. Two expert testers, consisting of a marine transportation lecturer and an information technology expert, assessed the prototype using a feasibility instrument covering button functionality, initial menu display, completeness and readability of satisfaction questions, presentation of satisfaction results, and overall feature functionality. TAPTAP provides public-side features for satisfaction surveys, complaints, and aspirations, as well as officer-side features for report monitoring and satisfaction-data visualization. The feasibility test produced scores of 80% from Tester 1 and 85.33% from Tester 2, indicating that the prototype is feasible for further pilot testing. The results show that TAPTAP can support more structured service feedback management at KSOP Bontang, although broader public-user testing, database implementation, data security validation, and integration with KSOP systems are still required before operational deployment